첫 번째와 두 번째 청각장애 자녀의 출산과 양육에 대한 어머니의 인식 비교 - 권순우(Soon-Woo Kwon); 김영한(Young-Han Kim) (언어치료연구, 2004)
청각장애를 가진 아동을 양육해야 하는 부모는 어떠한 부담을 가지고 있으며, 자녀 양육시 중요시 한 교육 목표, 가정에서의 교육 활동은 어떠했는지를 M학교에서 교육을 받고 있는 아동의 어머니 2명에게 심층 면담을 통해 자료를 수집하였다. 청각장애 자녀를 둔 부모의 양육 경험은 이 분야의 전문가들에게 중요한 정보를 제공해 줄 뿐만 아니라, 그 자체가 청각장애 아동의 교육과 재활에 중요 지침이 된다. 따라서 본 연구는 첫 번째와 두 번째 청각장애 자녀의 출산과 양육에 대한 어머니의 인식을 비교하여 이를 심층 분석함으로써 자녀의 청각장애를 합리적으로 이해하고 대처할 수 있도록 도움을 주는데 의의가 있다. The purpose of this study is to find out what the mother who should bringing up their children with hearing impairment have any burden and in rearing up, what mothers have important educational goals and educational activities at home. To achieve the purpose of this study, this study are gathered data through deep interview to two mothers of children with hearing impairment who have educated at M school. Maternal rearing experience with children with hearing impairment not only serve critical information, but also, itself is to be important guide for education and rehabilitation of children with hearing impairment. Therefore, this study are compared with between maternal rearing experience who have experienced the first children with hearing impairment and who have experienced the second children with hearing impairment through deep interview. This study helps mother with children with hearing impairment reasonably understand and copy with their children's disability. KCI Citation Count: 2